Penyuluhan Ecoprint untuk Menumbuhkan Karakter Peduli Lingkungan Sekitar di Kabupaten Kepulauan Meranti - Meldra, Delia Meldra; Mardamery; Sanusi; Mardiansyah, Yopy (Jurnal Tiyasadarma, 2024)
As technology grows, it also significantly influences changes in the quality of human life, which also affects the quality of the environment. The problem here is changes in human quality which are increasingly decreasing, namely throwing rubbish carelessly which pollutes the environment. To raise awareness and concern in protecting and utilizing the environment by introducing ecoprint. The method or approach used in this activity is a participatory approach. This approach is a practice of communicative, transactive, advocative and collaborative planning theories. This activity was carried out together with the women of PKK Pokja 2 Selatpanjang, Meranti Islands Regency. The result was that the women who took part in the counseling got creative ideas and really took part in activities using nature as a resource in making patterned cloth without using chemical dyes. The level of achievement of activities based on results and discussions is very good, where each stage produces good enthusiasm and desire. The benefits felt from this ecoprint counseling are: 1) Women get creative ideas for using nature; 2) Maintaining natural sustainability due to all natural processes; 3) Instill an environmentally caring mindset.